External and Middle Ear Trauma Resulting From Ear Impressions - Wynne, Michael K.; Kahn, Jonathan M.; Abel, Debra J.; Allen, Rose L. (Journal of the American Academy of Audiology, 2000)
When taking an impression of the external ear canal and ear, the audiologist is engaged in an invasive procedure whereby a foreign body is first placed into the ear canal and then removed. There is always an element of risk for significant medical problems when a clinician is performing an invasive procedure. Although some minor patient discomfort and, at times, some slight trauma to the ear canal occur when taking ear impressions, the incidence of significant trauma to the external or middle ear appears to be low. The purpose of this report is to provide some illustrative cases of significant external and middle ear trauma as a result of taking impressions of the external ear. Audiologists are advised to develop and implement an appropriate risk management program for taking ear impressions to reduce the potential risks associated with this procedure to their patients and to their practices.Abbreviations: CIC = completely in the canal, HPD = hearing protection device, OR = operating room, PROS = pressure relief oto-dam system
Keywords: Case study; ear impressions; foreign body; hearing aids; hearing protection devices; litigation; physical trauma; risk management; tympanic membrane perforation